Enhancing Educational Practices through AI and Data Visualization: Insights from a Community Engagement Workshop - Melissa Indah Fianty; Fahmy Rinanda Saputri (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community engagement explores the application of Artificial Intelligence (AI) and data visualization in the context of education through an interactive workshop. The workshop aims to enhance the capacity of high school teachers in Jakarta to utilize technology for data analysis using applications like Tableau. Participants engage in hands-on practice with four case studies: analysis of student performance by gender, the influence of parental education on student outcomes, evaluation of the effectiveness of exam preparation courses, and analysis of the impact of lunch programs on student achievement. Results indicate a significant improvement in participants' understanding and skills in using data to support evidence-based decision-making in educational settings.